Reviews. Issue 1 (1st June 2018) - Admirand, Peter; Murel, Jacob
Frank Miller's Daredevil and the Ends of Heroism, Paul Young (2017) New Brunswick, NJ: Rutgers University Press, 292 pp., ISBN: 9780813563817, p/bk, 28The Narratology of Comic Art, Kai Mikkonen (2017) New York: Routledge, 300 pp., ISBN: 978113822150, h/bk, 140.00